MINIMALLY INVASIVE TECHNIQUES IN THE INTEGRATED TREATMENT OF THOSE SUFFERING FROM SEVERE CONCURRENT INJURY WITH DOMINATING CHEST TRAUMA - E. A. Tseymakh; A. V. Bondarenko; A. A. Menshikov; A. V. Levin; P. E. Zimonin; A. V. Kazartsev (Туберкулез и болезни лёгких)
Treatment outcomes of 226 patients have been analyzed. Treatment and diagnostic algorithm has been developed for the management of patients with severe concurrent injury and dominating chest trauma. The indications for the following interventions have been formulated: emergency thoracotomy, emergency and urgent video-assisted thoracoscopy, local fibrinolytic therapy in case of clotted hemothorax and post-traumatic pleural empyema, valve bronchial block in tension and continuously persistent pneumothorax, osteosynthesis of fragmentary costal fractures. Using minimally invasive treatment techniques allowed decreasing the number of surgeries in the patients and increasing the number of recovered patients when discharged from the hospital.